(untitled) (Revista da Faculdade de Odontologia - UPF, 2015)
Aim: to evaluate in vitro the effectiveness of different chemical auxiliary substances used to promote decontamination of gutta-percha cones contaminated with different microorganisms. Material and methods: The microorganisms tested were strains of Enterococcus faecalis, Candida albicans, and Staphylococcus aureus. The 72 gutta-percha points were divided into three groups of 24 points, which were individually transferred into three tubes containing 5 ml of each bacterial suspension for 1 hour. The 24 gutta-percha points of each bacterial strain were randomly distributed into six groups (n=4) based on chemical auxiliary substance and period of decontamination, as follow: G1 (distilled water; DW); G2 (2.5% sodium hypochlorite; NaOCl); G3 (2.5% calcium hypochlorite; Ca(OCl)2); G4 (2% chlorhexidine gel; CHX); G5 (QMix); and G6 (6.5% grape seed extract; GSE). There were four evaluation periods (30, 60, 90, and 120 seconds). After disinfecting, the gutta-percha points were transferred to tubes containing 450 µL of sterile saline solution, homogenised, and diluted. Aliquots of 100 µL of the solution and the dilutions were cultivated in duplicate on plates containing blood agar. This material was incubated for 48 hours at 37 oC. Next, the number of colony-forming units (CFU/mL) were counted. Results: Groups G2 (NaOCl), G3 (Ca(OCl)2), G4 (CHX), and G5 (QMix) showed no bacterial growth of tested microorganisms at all periods of observation, and were statistically different from all other groups (p